2018
DOI: 10.1002/anie.201806583
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Active Molybdenum Phosphide Catalyst for Methanol Synthesis from CO and CO2

Abstract: Methanol is a major fuel and chemical feedstock currently produced from syngas, a CO/CO /H mixture. Herein we identify formate binding strength as a key parameter limiting the activity and stability of known catalysts for methanol synthesis in the presence of CO . We present a molybdenum phosphide catalyst for CO and CO reduction to methanol, which through a weaker interaction with formate, can improve the activity and stability of methanol synthesis catalysts in a wide range of CO/CO /H feeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 37 publications
10
63
0
2
Order By: Relevance
“…Therefore, the excess phosphorus forms oxide species. A previous study using XPS showed that oxidized Mo species form on the surface of a silica‐supported MoP catalyst upon exposure to air, and can be reduced using a pre‐reduction treatment prior to catalytic testing . The present study used the same pre‐reduction treatment, which is expected to reduce the surface phosphate or the oxide of molybdenum prior to catalytic testing.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Therefore, the excess phosphorus forms oxide species. A previous study using XPS showed that oxidized Mo species form on the surface of a silica‐supported MoP catalyst upon exposure to air, and can be reduced using a pre‐reduction treatment prior to catalytic testing . The present study used the same pre‐reduction treatment, which is expected to reduce the surface phosphate or the oxide of molybdenum prior to catalytic testing.…”
Section: Resultsmentioning
confidence: 95%
“…Before investigating promoter effects for HAS on MoP‐based catalysts, a systematic study was first performed to understand the effect of synthesis parameters on the structure and activity of the KMoP on amorphous SiO 2 catalyst system developed previously for MS from CO and CO 2 . The key parameters for synthesis are identified in the following sections as the P/Mo ratio, K/Mo ratio, and MoP loading.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations